Discrete Time Hazard Model with Interest Rate for Default Forecast: A Study of Post-2008-Crises In Indonesian Listed Insurance Companies - Ni Nyoman Sawitri (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
This paper is intended to examine the preformance of the discrete-time hazard model with interest rate in predicting bankruptcy of listed insurance companies in Indonesia Stock Exchange. The study focuses on the period after the 2008-crises. The study employed 2008-2015 financial data of all insurance companies listed in Indonesia stock market. The author conducted stepwise logistic regression to find particular financial ratios to be included in the model, and used interest rate as the baseline hazard rate. To examine precision of the model, the author placed 2016 as the forecast period.